Implementasi Nilai-nilai Karakter Disiplin dalam Pembelajaran Pendidikan Agama Islam di Sekolah Menengah Kejuruan (SMK) Negeri 1 Sungai Rumbai - Utami, Mughniya Tiara; Satria, Rengga (ANWARUL, 2023)
The purpose of this research is to find out the disciplinary character of students at SMKN 1 Sungai Rumbai, to find out the supporting factors and inhibiting factors in implementing disciplinary character in students and teachers' efforts in implementing disciplinary character in students. This research is a qualitative research with the type of case study. Data were collected through observation, in-depth interviews and documentation. After all data is obtained through data collection techniques, then the data is analyzed through a process of data management stages in the form of: data reduction, data presentation, conclusion drawing and verification. The results showed that: first, the implementation of disciplinary character values at the State Vocational High School 1 Sungai Rumbai was implemented through school rules and regulations. Second, the supporting factors for the implementation of character values at the State Vocational High School 1 Sungai Rumbai are good cooperation between fellow teachers, competent teachers. While the inhibiting factors are the different backgrounds of students, lack of awareness in students, and the environment outside the school. Third, the efforts made by Islamic Religious Education teachers in implementing disciplinary character values are by: habituation, exemplary, advice, gifts and punishment.